Dissolute characters : Irish literary history through Balzac, Sheridan Le Fanu, Yeats, and Bowen - McCormack, W. J. (William John), 1947- (Manchester Gothic (Manchester, England), 2017)
Radically revises the idea of a gothic tradition and traverses two centuries of Irish literary history to give a fluent and detailed account of the emerging relation between Irish culture, modernism and politics.